Transformational Leadership, Commitment, Rewards and Work Environment on Principal Performance - Sigid Susilo; Sarsono Sarsono; Istiatin Istiatin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The purpose of this study is to examine and analyze the influence of transformational leadership on principal performance. To examine and analyze the influence of commitment on principal performance. To determine the influence of rewards on principal performance. To determine the influence of the work environment on principal performance. This study uses a quantitative descriptive approach. Data collection techniques include observation, questionnaires, documentation, and literature review. The sampling technique used in this study was non-probability sampling with a saturated method, where the entire population was sampled. Data analysis techniques in this study used quantitative analysis, multiple linear regression analysis, and coefficient of determination analysis. The results of this study indicate that transformational leadership has a positive and significant effect on performance. Commitment has a positive and significant effect on performance, rewards have a positive and significant effect on performance, and the work environment has a positive and significant effect on performance. Transformational leadership, commitment, rewards, and the environment collectively have a positive and significant effect on the performance of school principals within the Central Java Region VI Education Office.